Lost diaries or in the system of education of law - González Ballar, Rafael (2015)
This article refers to legal education according to current requirements. This work is the result of some comments made to the presentation of the book "Critic of the Teaching of Law" by Prof. Dr. Alex Solis. Thus, some of the ideas that Dr. Solis presents in his book, and the related comments and ideas of the author in relation to the system of legal education in Costa Rica are presented